ANTIBIOTIC PROPHYLAXIS CESAREAN SECTION - Huamán Guerrero, Moisés (2015)
In a prospective study of patients without evidence of infection, which were cesarean, postoperative infectious morbidity was assessed. In a group ampicillin he was given 8.8 days, in a second group ampicillin was used in the perioperative and a third group received no antibiotic. Postoperative infectious complications (endometritis, wound infection, urinary tract infection, pelviperitonitis) were significantly less frequent in patients in whom preoperative antibiotic prophylaxis was used in the other 2 groups. Ampicillin resistance of germs grow observed was achieved. Therefore, in our hospital we would recommend the preoperative use of ampicillin or not use any prophylactic antibiotic in cesareada woman, because of side effects and disadvantages and dangers of indiscriminate use of ampicillin.